MY AFTERNOONS WITH MARGUERITTE: A SENSITIVE LOOK AT THE INCLUSION OF CHILDREN WITH ASD - Benvindo de Souza, Cirlene; Antonia da Silva, Ivone (Revista Gênero e Interdisciplinaridade, 2024)
This review offers us a sensitive look at the inclusion of children with ASD. It highlights the importance of mutual respect and acceptance of differences. Evidenced through understanding special needs. Thus, this review, the object of a critical analysis, beautifully explains how genuine connection between people can overcome obstacles and enrich lives.